Ability to consent to a sexual assault medical forensic examination in adult patients with serious mental illness. (January 2022) - Miles, Leslie W.; Knox, Eleanore; Downing, Nancy; Valentine, Julie L.
Abstract: When a patient reporting a sexual assault (SA) presents with signs and symptoms of serious mental illness (MI), medical providers or forensic examiners may have concerns regarding the ability to legally consent to a sexual assault medical forensic examination (SAMFE). Numerous encounters have occurred where a SAMFE was not offered to a cooperative adult patient because the patient exhibited signs and symptoms of MI. Medical providers and examiners may be motivated by beneficence (believing that treating the patient's MI must take priority over the SAMFE) and/or non-maleficence (a concern that the in-depth SAMFE may worsen the patient's psychological state). Situations where a patient has received psychiatric medications or is under involuntary psychiatric detention also raise capacity to consent to SAMFE concerns. This review explored these concerns and provides recommendations for conducting SAMFEs in adult patients with MI. In instances where a patient has the capacity and is cooperative, the decision to undergo, postpone, or decline a SAMFE ought to be ultimately made by the patient, rather than on their behalf by the provider, SANE or forensic examiner.